The influence of psychological determinants on visitors' future behavioural intentions in smallscale events sports tourism - Anisah, Abdul Wafi (2020)
Small-scale events in sports tourism (SSEST) play an important role in contributing to the economy of various destinations and the local community. Despite the diversity of research in the marketing and managing of sporting events, limited studies have been conducted on sports tourism events in Malaysia, especially with regards to visitors’ psychological behaviours. Hence, the purpose of this study is to examine the influence of motivation, perceived image, perceived value, and satisfaction on visitors’ future behavioural intentions for attending small-scale events in sports tourism. This study has chosen the Theory of Planned Behaviour, the Tourist Attraction Theory and the Push and Pull Theory as theoretical backgrounds. Data was collected from self-administered questionnaires among 468 visitors who attended selected small-scale events in sports tourism in the northern region of Peninsular Malaysia. This study generally found that perceived value factors highly influenced visitors’ decisions to attend an event, followed by the motivation factor. This study also discovered direct and indirect relationships among those variables, which have been analysed using Structural Equation Modeling using AMOS (SEM-AMOS). Findings revealed that all variables have a direct relationship with visitors’ future behavioural intentions. Meanwhile, in terms of an indirect relationship, results indicated that visitors’ satisfaction partially mediates the relationship between motivation, perceived image and perceived value towards future behavioural intentions. This study contributes to the body of knowledge with a proposed model that reveals an association between motivation, perceived image, perceived value, satisfaction, and behavioural intentions among visitors’ participating in SSEST. In addition, this study has concluded that, in order to attract visitors to attend small scale sports tourism events, organisers should enhance their understanding of visitors’ perceived values. Furthermore, state tourism authorities should design and plan strategies to develop small-scale events that are comparable to mega-sporting events as local products that will be able to attract tourists.